Scoping Review: Factors Causing Claim Pending in Indonesian Hospitals - Zalukhu, Linna Asni; Permanasari, Vetty Yulianty (Syntax Corporation Indonesia, 2025)
Pending claims are one of the crucial problems often faced by hospitals in the National Health Insurance (JKN) financing system. This condition not only causes disruptions to hospital cash flow but also reflects weaknesses in the claims management system administratively, technically, and systemically. This study aims to identify and map various factors causing pending BPJS Kesehatan claims in Indonesian hospitals through a scoping review approach. The review process was carried out with reference to the Arksey and O'Malley framework and the PRISMA-ScR guidelines, using literature sources from Google Scholar, Garuda, PubMed, and Neliti databases. Article selection was conducted systematically for publications from 2022–2024, in Indonesian, available in full-text form, and indexed at least SINTA 3. Of the 268 articles identified, 10 met the inclusion criteria and were further analyzed. The results of the synthesis show that the causative factors of pending claims can be grouped into five main themes: inaccuracy in coding diagnosis and procedures, incompleteness of claim documents, limitations of information systems, low competence of human resources, as well as inconsistencies in the implementation of SOPs and weak coordination between units. This study concludes that pending claims are multifactorial and interrelated, requiring comprehensive intervention in the form of strengthening human resource capacity, optimizing the digital claims system, and improving hospital claims policies and governance systemically.